2017
DOI: 10.1016/j.neo.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A MicroRNA/Ubiquitin Ligase Feedback Loop Regulates Slug-Mediated Invasion in Breast Cancer

Abstract: The transformation of a normal cell to cancer requires the derail of multiple pathways. Normal signaling in a cell is regulated at multiple stages by the presence of feedback loops, calibration of levels of proteins by their regulated turnover, and posttranscriptional regulation, to name a few. The tumor suppressor protein FBXO31 is a component of the SCF E3 ubiquitin ligase and is required to arrest cells at G1 following genotoxic stresses. Due to its growth-suppression activity, it is underexpressed in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Furthermore, it was suggested that FBXO31 targets mouse double minute 2 homolog (MDM2) during ubiquitination and degradation, leading to elevated p53 levels, cell cycle arrest and growth inhibition, supporting the tumor suppressive role of FBXO31 in breast cancer ( 27 ). In addition, Manne et al ( 39 ) demonstrated that FBXO31 targets the Snail family transcriptional repressor protein 2 (Slug), which is involved in the epithelial-mesenchymal transition, cell invasion, ubiquitination and degradation, and therefore represses the growth of breast cancer cells. Studies have determined that micro (mi)RNAs are dysregulated at all stages of breast cancer and serve important roles in tumorigenesis, invasion and metastasis ( 40 , 41 ).…”
Section: Fbxo31 As a Tumor Suppressormentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was suggested that FBXO31 targets mouse double minute 2 homolog (MDM2) during ubiquitination and degradation, leading to elevated p53 levels, cell cycle arrest and growth inhibition, supporting the tumor suppressive role of FBXO31 in breast cancer ( 27 ). In addition, Manne et al ( 39 ) demonstrated that FBXO31 targets the Snail family transcriptional repressor protein 2 (Slug), which is involved in the epithelial-mesenchymal transition, cell invasion, ubiquitination and degradation, and therefore represses the growth of breast cancer cells. Studies have determined that micro (mi)RNAs are dysregulated at all stages of breast cancer and serve important roles in tumorigenesis, invasion and metastasis ( 40 , 41 ).…”
Section: Fbxo31 As a Tumor Suppressormentioning
confidence: 99%
“…Subsequently, the tumor suppressive effect of miR-210 downregulation may be reversed by further depletion of FBXO31. A study by Manne et al ( 39 ) indicated that the oncogenic miRNAs miR93 and miR106a repressed FBXO31 expression, thus impairing the degradation of Slug via FBXO31.…”
Section: Fbxo31 As a Tumor Suppressormentioning
confidence: 99%
“…FBXO31 targets and ubiquitylates Slug for proteasomal degradation. Due to its growth-suppression activity, it is underexpressed in many kinds of cancers [53]. High-regulation of FBXO31 inhibits the proliferation and colony formation of breast tumor cells by mediating ubiquitination and degradation of spci c substrates, and then inhibits cancer progression [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that in the context of breast cancer miR‐93 and miR‐106a, which repress the E3 ligase FBXO31 that targets the pro‐metastatic Slug, are downregulated. This mechanism is repressed in metastatic breast cancer where high miR‐93 and miR‐106a levels ensures that Slug is expressed, which was then shown to further potentiate miR‐93 and miR‐106a levels by establishing a positive feedback loop (Manne et al, ). Hence, another alternative mechanism can be that increased PCBP1 expression during LPS‐induced ALI directly increases pro‐inflammatory cytokines by increasing their transcription in a similar feed‐forward mechanism.…”
Section: Discussionmentioning
confidence: 99%